Are We Still Going Through the Empty Ritual of Participation? Inner-City Residents' and Other Grassroots Stakeholders' Perceptions of Public Input and Neighborhood Revitalization. (May 2020) - Silverman, Robert Mark; Taylor, Henry Louis; Yin, Li; Miller, Camden; Buggs, Pascal
This article revisits Arnstein's "ladder of citizen participation" focusing on inner-city residents' perceptions of public input in neighborhood revitalization projects. It draws from data collected in Buffalo, New York for a larger project that aimed to address negative externalities caused by neighborhood change. Data were collected using focus groups in neighborhoods in the early stages of revitalization. Nine focus groups took place across three neighborhoods experiencing encroachment from hospitals and universities. Data analysis was guided by standpoint theory, which focuses on amplifying the voices of groups traditionally disenfranchised from planning processes. The findings suggest that the shortcomings of public input identified by Arnstein a half century ago remain problematic. Residents continue to perceive limited access to urban planning processes and believe outcomes do not prioritize their interests. This is particularly problematic in minority, working-class neighborhoods when institutionally driven development occurs. Recommendations emphasize enhancing planners' fidelity to strategies that expand citizen control.